Sarcolemmal nNOS anchoring reveals a qualitative difference between dystrophin and utrophin. - Li, D; Bareja, A; Judge, L; Yue, Y; Lai, Y; Fairclough, R; Davies, K; Chamberlain, J; Duan, D (2010)
Duchenne muscular dystrophy (DMD) is a lethal muscle disease caused by dystrophin deficiency. In normal muscle, dystrophin helps maintain sarcolemmal stability. Dystrophin also recruits neuronal nitric oxide synthase (nNOS) to the sarcolemma. Failure to anchor nNOS to the membrane leads to functional ischemia and aggravates muscle disease in DMD. Over the past two decades, a great variety of therapeutic modalities have been explored to treat DMD. A particularly attractive approach is to increase utrophin expression. Utrophin shares considerable sequence, structural and functional similarity with dystrophin. Here, we test the hypothesis that utrophin also brings nNOS to the sarcolemma. Full-length utrophin cDNA was expressed in dystrophin-deficient mdx mice by gutted adenovirus or via transgenic overexpression. Subcellular nNOS localization was determined by immunofluorescence staining, in situ nNOS activity staining and microsomal preparation western blot. Despite supra-physiological utrophin expression, we did not detect nNOS at the sarcolemma. Furthermore, transgenic utrophin overexpression failed to protect mdx muscle from exercise-associated injury. Our results suggest that full-length utrophin cannot anchor nNOS to the sarcolemma. This finding might have important implications for the development of utrophin-based DMD therapies.